2019
DOI: 10.1111/jcmm.14174
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of a radiation‐induced dermatitis rat model

Abstract: Radiation‐induced dermatitis is a common and serious side effect after radiotherapy. Current clinical treatments cannot efficiently or fully prevent the occurrence of post‐irradiation dermatitis, which remains a significant clinical problem. Resolving this challenge requires gaining a better understanding of the precise pathophysiology, which in turn requires establishment of a suitable animal model that mimics the clinical condition, and can also be used to investigate the mechanism and explore effective trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 60 publications
3
17
0
Order By: Relevance
“…“Radiation-irritated skin” is a brand-new concept of the sequelae of radiation therapy that no one reported in the past. According to previous studies, [ 6 , 12 , 14 , 15 ] we concluded that the possible pathological mechanism of “Radiation-irritated skin” may consist of changes such as thickening of epidermis, hyperkeratosis, and atrophy of sweat gland and sebaceous gland.(Fig. 3 ) In this study, 46.3% of breast cancer patients after whole breast radiotherapy may develop “radiation-irritated skin”.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…“Radiation-irritated skin” is a brand-new concept of the sequelae of radiation therapy that no one reported in the past. According to previous studies, [ 6 , 12 , 14 , 15 ] we concluded that the possible pathological mechanism of “Radiation-irritated skin” may consist of changes such as thickening of epidermis, hyperkeratosis, and atrophy of sweat gland and sebaceous gland.(Fig. 3 ) In this study, 46.3% of breast cancer patients after whole breast radiotherapy may develop “radiation-irritated skin”.…”
Section: Discussionsupporting
confidence: 53%
“…Similarly, skin accessory tissues such as sweat glands, sebaceous glands, and hair follicles are also sensitive to radiation. In rat model, irradiation to the skin will result in irreversible pathological changes such as sebaceous glands loss, hair follicles loss, increased epidermal thickness, and skin fibrosis [ 6 , 15 ]. We found skin dryness and hotness in the radiation field impacted the quality of life of breast survivors after radiotherapy and led to inferiority or depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of this, results corroborate what has been described for the skin that covers the most regions of the body [28,29], related with drastic but temporary atrophy of sebaceous glands and hair follicles. We found that between day 4 and day 14, these epidermal components disappeared.…”
Section: Discussionsupporting
confidence: 89%
“…Radiation‐induced dermatitis can cause skin fibrosis, and radiation also damages mitochondria 108 . Radiation-induced subcutaneous fibrosis can also be associated with genetic variation of thioredoxin reductase 2 (Txnrd2), a mitochondrial enzyme involved in removal of ROS 109 .…”
Section: Mitochondrial Dysfunction In Tissuesmentioning
confidence: 99%